Site Selection for Restoration Planning: A Protocol With Landscape and Legislation Based Alternatives - Gama, Veronica F.; Martensen, Alexandre C.; Ponzoni, Flavio J.; Hirota, Marcia M.; Ribeiro, Milton C. [UNESP] (Assoc Brasileira Ciencia Ecologica E Conservacao, 2013)
Selecting sites for ecological restoration is an imperative, although challenging task. We developed a spatially explicit model to support site design and prioritization towards ecological restoration. We considered seven distinct and flexible templates, two based on legislation requirements and five on landscape spatial parameters, such as corridor design, enhancements in patch size and shape, and proximity to larger sources areas, thus, with different resilience capacities. We tested the approach on two different scales of analysis: applying the legislation based templates in the Atlantic Plateau of Sao Paulo, which is part of the Atlantic Forest biome, and the landscape based templates in one of its sub-watersheds (similar to 150,000 ha), and then calculated landscape indexes to compare the current forest configuration to the resulted simulated restored ones. We showed that our protocol is flexible, transparent and repeatable, thus, could help in decision making towards conservation management.
Keywords: Restoration Planning; Connectivity; Fragment Size; Site Selection; Spatially Explicit Simulations